Impact of the COVID-19 pandemic on the psychological aspects and mental health of elite soccer athletes: a systematic review - Andrade, Alexandro; D'Oliveira, Anderson; Neiva, Henrique Pereira; Gaertner, Gilberto; da Cruz, Whyllerton Mayron (Frontiers in Psychology, 2024)
Introduction: Investigation of the psychological impact on soccer athletes during the pandemic is essential given their unique challenges, including training disruptions and competition postponements. Understanding these effects will allow the development of specific strategies to preserve the mental health and performance of elite athletes, contributing to effective interventions with both short and long-term benefits. Objective: To analyze the impact of the COVID-19 pandemic on the psychological aspects and mental health of elite soccer athletes. Method: The review adhered to PRISMA criteria, and the study protocol was registered in the International Prospective Register of Systematic Reviews (CRD42022341545). Searches were conducted until July 2023 in databases including Cochrane, PsycINFO, PubMed, Scopus, SPORTDiscus, and Web of Science. Only original, peer-reviewed studies in English, Portuguese, or Spanish assessing the impact of the COVID-19 pandemic on the psychological aspects and mental health of elite soccer athletes were included. Results: The search identified 1055 records and 43 studies were included in this review between 2020 and 2023. In total, the sample included 16,321 soccer athletes of different age groups. Anxiety, depression, mood states, and mental well-being were the most investigated variables. Increased levels of anxiety, depression, and worsening mental well-being were observed in elite soccer athletes. Maintaining fitness during the pandemic showed positive results. Other variables, such as coping, resilience, and sleep quality monitoring, were less widely investigated. Evaluating methodological quality was considered regular for observational and experimental studies. Conclusion: The study reveals a negative impact of the COVID-19 pandemic on elite soccer athletes, considering psychological aspects and their mental health, notably heightened anxiety and depression. Observational methods predominated, showing mood swings linked to individual characteristics and fitness maintenance efforts. Studies with better-designed methodological approaches and controlled experimental interventions are recommended in the future to mitigate the negative effects of the pandemic on soccer players.